Liberalizacja usług w świetle orzecznictwa Trybunału Sprawiedliwości UE - Maciejczyk-Krysiak, Nina (Kwartalnik Prawa Publicznego, 2016)
The Treaty on the functioning of the European Union introduces in Article 26 Sec. 2 a definition of the internal market, which is an area without internal frontiers and in which the free movement of goods, persons, services and capital is ensured. According to the wording of Article 57 TFEU, services are usually provided for remuneration insofar as they are not covered by the provisions on the free movement of goods, capital and persons. The enumerated list of various economic activities covered by the EU principle of freedom to provide services is exemplary and does not cover all the activities that are protected under the EU law. This leads to the conclusion that an in-depth analysis of the freedom to provide services, especially in the context of its recent liberalization, is not possible without reference to the extremely rich case law of the Court of Justice of the European Union (formerly ECJ). The scope of this article is an analysis of this case law of the Court of Justice of the EU (formerly ECJ) in the context of the liberalization of services, taking place not only within the EU regime, but also within the WTO/GATS.